DIASPORIC CONSCIOUSNESS IN AMITAV GHOSH’S THE SHADOW LINES AND SEA OF POPPIES - Dr. Ritu Kumaran; Smt. Pooja Tandon (International journal of economic perspectives, 2022)
Diaspora is a psychological journey, a dilemma between homeland and new settlement nations. The migrant, journeying from place to place becomes a stranger in other land and this alienation makes an effect on identity psychological peace and existential status. Diasporic writing occupies a place of great significance between countries and cultures. Diasporic writing mostly become a response to the lost homes and to issues such as Dislocation, Nostalgia, Discrimination, survival, Cultural change and identity. Dislocation is one of the first feelings that haunt the diasporic community. When diasporic people find themselves dislocated from the home society they are upset mentally and strive to remember and locate themselves in a nostalgic past. Amitav Ghosh, a novelist with an extraordinary sense of history and place, is indisputably one of the most important novelists of our time. As a writer of Indian Diaspora